Productivity and physiological quality of bean plants seeds subjected to drying by herbicides in different phenological stages (Bioagro, 2022)
The use of herbicides in the pre-harvest of cowpea beans seeks to increase the uniformity of maturation of plants and pods. The objective of this work was to evaluate the productivity and physiological quality of bean seeds in plants subjected to desiccation promoted by herbicides applied in two phenological stages. Two experiments were conducted, in field and laboratory. In the field, a randomized block design was developed in a factorial scheme (3x2+1). Diquat (2 L·ha-1), flumioxazin (60 g·ha-1), and the mixture of both products (di-flu) were used in two phenological stages of application (80 and 90 % of the mature pods), repeated four times. A control treatment (without herbicide) was included. In the field, productivity and performance variables were evaluated. In the laboratory, the physiological quality of the seeds was evaluated. Herbicides applied with 80 % and 90 % mature pods did not influence grain yield. Diquat and di-flu anticipated harvest in six days without affecting bean yield. The desiccation with 90 % of ripe pods positively influenced the quality of seed. The application of the herbicide to the plants in the phenological stage of 80 % of mature pods negatively influences the quality of the bean seed.
Keywords: Germination; harvest anticipation; physiological maturity; Vigna unguiculata